(untitled) - RIZKY ADHANI, AKBAR (Jurnal Ilmu Manajemen (JIM), 2013)
This research was conducted to examine the effect of selfactualizationneeds,workload,andjobperformance.Theobjectiveof research to know the influence of self-actualization needs andworkload toward job performance on PT. Bank Tabungan Negara(Persero),Tbk Kantor Cabang Syariah Surabaya. This study used asaturated sampling by the number of 43 respondens by using causalresearch. The analysis used is multiple regression analysis by usingSPSS for windows in seeing the independent variables influence thedependent variable either jointly or individually. The results showedthat self-actualization needs significantly influence toward jobperformance and workload had no significant influence toward jobperformance, whereas self-actualization and workload together hadno significant influence toward job performance.Keywords: self-actualization needs, workload, and job performance.